Shades of whiteness: The appropriation of religious symbols by the Nordic Alt-Right - Butters Albion (Donner Institute, 2025)
This study examines the appropriation of religious symbols by the Nordic Alt-Right over the last decade, focusing on their use for völkisch identity construction around whiteness. It locates this signification historically, both before and during the Third Reich, to reveal a complex genealogy complicated by racial ideals, nationalistic agendas and magical thinking. Analysis centres around a selection of symbols – ranging from various Norse runes to the Valknut, the Sonnenrad and the swastika – used both explicitly and in more private contexts by members of the Nordic Alt-Right, with special attention focused on two groups that are active today, the Nordic Resistance Movement and the Soldiers of Odin. This opens a discussion on the semiotic range of appropriation itself, in order to expose how it is operative in different ways and on different levels, not only in terms of cultural borrowing or contestations of meaning but as an appropriation of ideological frames and systems of belief.